III-nitrides light emitting diodes: technology and applications - Li, Jinmin; Wang, Junxi; Yi, Xiaoyan; Liu, Zhiqiang (Springer series in materials science, 2020)
The book provides an overview of III-nitride-material-based light-emitting diode (LED) technology, from the basic material physics to the latest advances in the field, such as homoepitaxy and heteroepitaxy of the materials on different substrates. It also includes the latest advances in the field, such as approaches to improve quantum efficiency and reliability as well as novel structured LEDs. It explores the concept of material growth, chip structure, packaging, reliability and application of LEDs. With spectra coverage from ultraviolet (UV) to entire visible light wavelength, the III-nitride-material-based LEDs have a broad application potential, and are not just limited to illumination. These novel applications, such as health & medical, visible light communications, fishery and horticulture, are also discussed in the book